A Theory of Wage Dispersion and Job Market Segmentation - Weitzman, Martin L. (Quarterly Journal of Economics, 1989)
Job market segmentation refers to the idea that there tends to be a correlation among high wages, high productivity, high capital intensity, high value added, few quits relative to layoffs, and low labor turnover. This paper develops a model of wage dispersion and job market segmentation based on the very sparse assumption that the only departure from a strictly orthodox neoclassical world consists of wages being sticky in the short run. Implications of the model are explored and discussed.